THE APPLICABILITY OF THE BRADEN SCALE IN THE PREVENTION OF PRESSURE INJURIES IN THE ICU - Paula Gomes da Silva, Ana; Silva Oliveira, Geane; Caroline de Souza, Anne; de Lira Silva, Macerlane (Health and Society, 2023)
Introduction: One of the main consequences resulting from the long stay in the scope of Intensive Care Units (ICU) is the occurrence of pressure injuries (PPL), in the vast majority of cases, due to medical devices, such as catheters and probes, as well as such as insufficient blood flow to bony prominences. Objective: In view of the above, the objective was, through the scientific literature, to know the applicability of the Braden scale in the prevention of pressure injuries in the intensive care unit. Methodology: This is an integrative literature review, based on scientific articles related to the topic. The bibliographic search will be carried out from December 2022 to January 2023, in the following databases: LILACS, MEDLINE, IBECS and BDENF, with the following Health Sciences Descriptors (DeCS): “Pressure Injury”; “Risk Measurement”; “Intensive Care Units” using the Boolean operator AND. Inclusion Criteria: complete articles, available for download; published in Portuguese and from the last 05 years. Exclusion criteria: duplicate articles in databases and monographs. The results found were demonstrated in a qualitative way, through information collected through secondary sources of bibliographic review. Results and Discussion: The results showed that the use of the Braden Scale preserves the integrity of the patient’s skin, considering that injury prevention is an important component of nursing practice and helps to identify potential risk factors that can lead to to the development of pressure ulcers in ICU patients. In summary, risk assessment instruments and preventive measures such as the Braden Scale can help professionals in the prevention of pressure ulcers. Conclusion: However, prevention of incontinence-related injuries, nutritional diagnosis, nutritional interventions to prevent injuries, and care related to medical devices have been shown to be components of care.